Tujuan Pendidikan dan Kaedah Pengajaran Abu Hanifah dalam Kitab al-‘Alim wa al-Muta‘allim - Mamat, Mohd Anuar; Wan Abdullah, Wan Suhaimi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2010)
The purpose of education and the methods of teaching are important variables in the process of education. They are closely related to the effort to realize quality education and effective teaching. This article presents these two elements as treated by Abu Hanifah in his al-‘Alim wa al-Muta‘allim. The said text has been documented based on the dialogue between Abu Hanifah (al-‘Alim) and one of his disciples (al-Muta‘allim). This study will present an analysis on the purpose of education according to Abu Hanifah and his teaching methods as seen in this text.